Do generic gTLDs require their own ex ante regulation?. Issue 3 (1st September 2016) - Cormack, Andrew
Abstract : This article reviews ICANN's treatment of applications to create new Top Level Domains based on generic terms (e.g. .book, .motorcycles ), reserved for exclusive use by the applicant. It finds little evidence in past domain name history that such registrations represented a risk to competition. Had applicants made abusive use of their domains then existing law would have provided appropriate remedies in any case. Theory suggests that such a novel market was unsuitable for prospective regulatory action and that, by converting potential monopolies into potential cartels, ICANN's action may even have made the competition risk worse.